User management and moderating violations according to company policies of BIGO Technology PTE. LTD-(LIKEE) - Abudarda, K.A.M (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.